MAKNA SOLIDARITAS SEBAGAI NILAI KONSELING ISLAM DALAM BUDAYA KEMBANG ENDOG-ENDOGAN SUKU OSING BANYUWANGI - M. Wildan; M.Syakur (Fakultas Dakwah Universitas Ibrahimy, 2023)
Indonesia is a country that has a diversity of tribes, ethnicities, cultures, races and religions. Living in a country is a gift for the people, because in their environment they are surrounded by culture, with these various cultures contributing greatly to the survival of the community, especially the creation of solidarity and harmony in social life. The creation of solid and harmonious social relations cannot be separated from the role of culture that grows around the community. Practically this research aims to describe the meaning of solidarity as the value of Islamic counseling in the culture of the endog-endogan flower of the Osing Banyuwangi tribe. The research method used is qualitative research with ethnographic types. The results of this study can be concluded that the meaning of solidarity as an Islamic counseling value in the culture of the endog-endogan flower of the Osing Banyuwangi tribe gives birth to positive values that can be lessons in wading through social life, namely fostering a sense of togetherness among citizens, creating enthusiasm, magnetic power, fostering an attitude of not distinguishing social status and age, fostering a sense of caring, a sense of familiarity, an egalitarian attitude as a human being, an attitude of mutual help, an attitude of gratitude, an attitude of sharing and an attitude of tolerance towards non-Muslims.